Methods and Models for Building an Interface for Digital Information Infrastructure Smart Gallery - Simeonov, Stanislav; Gospodinova, Ekaterina (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2022)
This paper aims to demonstrate some solutions of a new method for constructing modal interfaces for information structure of a smart Gallery, which allows using the context-oriented calculations and subject-oriented knowledge base to offer the user the most suitable interface, based on available resources, situations, context, preferences and constraints. The developed foundations are based on subject-oriented knowledge bases.